Pengaruh Konservatisme Akuntansi dan Corporate Social Responsibility Disclosure terhadap Kualitas Laba melalui Manajemen Laba pada Perusahaan Manufaktur yang Terdaftar di BEI - Jeni Bulangtimuhe; Herman Darwis; Rena Mustari Mokoginta (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to analyze the effect of accounting conservatism and Corporate Social Responsibility Disclosure on earnings quality through earnings management in manufacturing companies listed on the Indonesia Stock Exchange for the 2021–2024 period. This study uses a quantitative approach with secondary data obtained from annual reports and company financial statements. The research sample was selected using a purposive sampling method. Data analysis was conducted using panel data regression and a mediation test. The results show that accounting conservatism has no effect on earnings quality, while Corporate Social Responsibility Disclosure and earnings management have an effect on earnings quality. Furthermore, accounting conservatism has no effect on earnings management, while Corporate Social Responsibility Disclosure has an effect on earnings management. The results of the mediation test indicate that accounting conservatism has no effect on earnings quality through earnings management, while Corporate Social Responsibility Disclosure has an effect on earnings quality through earnings management. Thus, earnings management is able to mediate the effect of Corporate Social Responsibility Disclosure on earnings quality, but is unable to mediate the effect of accounting conservatism on earnings quality.